The Role of TL1A and DR3 in Autoimmune and Inflammatory Diseases - Yoshihiro Aiba; Minoru Nakamura (Hindawi Limited, 2013)
TNF-like ligand 1A (TL1A), which binds its cognate receptor DR3 and the decoy receptor DcR3, is an identified member of the TNF superfamily. TL1A exerts pleiotropic effects on cell proliferation, activation, and differentiation of immune cells, including helper T cells and regulatory T cells. TL1A and its two receptors expression is increased in both serum and inflamed tissues in autoimmune diseases such as inflammatory bowel disease (IBD), rheumatoid arthritis (RA), and ankylosing spondylitis (AS). Polymorphisms of the TNFSF15 gene that encodes TL1A are associated with the pathogenesis of irritable bowel syndrome, leprosy, and autoimmune diseases, including IBD, AS, and primary biliary cirrhosis (PBC). In mice, blocking of TL1A-DR3 interaction by either antagonistic antibodies or deletion of the DR3 gene attenuates the severity of multiple autoimmune diseases, whereas sustained TL1A expression on T cells or dendritic cells induces IL-13-dependent small intestinal inflammation. This suggests that modulation of TL1A-DR3 interaction may be a potential therapeutic target in several autoimmune diseases, including IBD, RA, AS, and PBC.